EXPERIMENTAL INVESTIGATIONS ON METHANOL FUELLED D.I DIESEL ENGINE WITH CATALYTIC COATINGS ASSISTED BY GLOW PLUG - R, Suresh.; Bose.R, Subash Chandra; K, Arumugam.; R, Anbazhagan.; V, Sathiyamoorthy. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
A comprehensive study on the methanol with three different types of Catalytic coatings assisted by Glow Plug is discussed in this paper. A four stroke single cylinder water cooled D.I diesel engine was adopted for the experiment. The present study aims to evaluate the Performance and Emission characteristics level of methanol fuel with three types of catalytic coatings assisted by Glow Plug. The catalytic coatings have established enhanced rate of combustion, which results in increased brake thermal efficiency. These methods of coating are selected based on generally available technologies and reviews of several researchers through their literature reviews. In this study, the diesel engine was tested using methanol coated with three types of catalytic coatings namely Copper, Aluminium oxide, and Chromium oxide and assisted by Glow Plug respectively. The influence of various catalytic coatings in combustion chamber(cylinder head inner surface, piston, valve) results in tremendous changes in the various parameters of the GHSI engine. The Exhaust temperature for Copper coating was higher compared to Aluminium oxide coating and Chromium oxide coating. It is noticed that, brake thermal efficiency was thus improved in almost all operation conditions with the Methanol fuels. The HC and CO emissions are higher at Methanol fuelled with Copper coating. NOx and Smoke emissions are lower for Chromium oxide coating compared to Copper coating and Aluminium oxide coating. Among all coatings, Copper coating exhibits better efficiency and lower emission compared to other coatings.